Cognitive Apprenticeship Improves Self Efficacy At Aviation Polytechnic Of Surabaya - Setiyo; Yatim Riyanto; Luthfiyah Nurlaela (Journal of Education and Vocational Research, 2019)
Internships are a method of connecting learning in schools with actual work powered by experts in the field of work. Self-efficacy skills are very necessary in the world of work. Self efficacy is, a person’s belief in carried out their duties. The research purpose determined the effect of cognitive apprenticeship on students self efficacy in Flight Polytechnics. The research method used ANOVA with the experimental and control groups, with 140 research subjects. The results showed the influence of cognitive apprenticeship on self efficacy. Self-efficacy ability is needed in the world of work, because it relates to one’s success in doing work. Vocational education aims to prepare a skilled workforce. Internships are a means to bring students closer to the world of work. Soft skills in vocational education must be developed. The apprentice is able to bring the development of soft skills to students. Workers with self-efficacy skills are needed in the industrial era.